U.S. Cattle Producer Adoption of Secure Beef Supply Plan Enhanced Biosecurity Practices and Foot-and-Mouth Disease Preparedness - Pudenz, Christopher C.; Mitchell, James L.; Schulz, Lee L.; Tonsor, Glynn T. (Frontiers in Veterinary Science, 2021)
The prospect of a foot-and-mouth disease (FMD) outbreak in U.S. livestock populations has motivated the development of the Secure Beef Supply (SBS) Plan, which includes a comprehensive list of enhanced biosecurity practices that aim to prevent FMD transmission and facilitate continuity of business during an outbreak. While FMD poses a serious threat to livestock production in the United States, little is known about producers' uptake of the enhanced biosecurity practices included in the SBS Plan. In this study, we benchmark adoption and feasibility-of-adoption perceptions for U.S. cattle producers. Our results show adoption of the 13 enhanced biosecurity practices is generally low. Especially concerning is the low adoption of the three strongly-recommended pre-outbreak practices—having a biosecurity manager, having a written operation-specific enhanced biosecurity plan, and having a line of separation. Adoption of the pre-outbreak practices is likely low because the benefits of adopting the practices depend on a low probability, uncertain event. That said, producers who have adopted the pre-outbreak practices are more likely to have higher feasibility ratings for the remaining enhanced biosecurity practices, suggesting that adoption of the strongly recommended practices is associated with adoption of all enhanced biosecurity during an FMD outbreak. Complementarity is examined and shows that adoption of the pre-outbreak practices coincides with adoption of the outbreak-specific practices. Taken together, our results suggest that adoption of the strongly recommended pre-outbreak practices could help facilitate a quicker and more effective U.S. cattle industry response to an FMD outbreak in the United States.